Migraine prevalence, alexithymia, and post-traumatic stress disorder among medical students in Turkey - Balaban, Hatice (Springer Milan, 2012)
The aim of this study was to investigate the prevalence of migraine, alexithymia, and post-traumatic stress disorder among medical students at Cumhuriyet University of Sivas in Turkey. A total of 250 medical students participated in this study and answered the questionnaires. The study was conducted in three stages: the self-questionnaire, the neurological evaluation, and the psychiatric evaluation. In the first stage, the subjects completed a questionnaire to assess migraine symptoms and completed the three-item Identification of Migraine Questionnaire, the Toronto Alexithymia Scale, and the Post-Traumatic Stress Disorder Checklist-Civilian Version Scale. The subjects who reported having a migraine underwent a detailed neurological evaluation conducted by a neurologist to confirm the diagnosis. In the final stage, the subjects with a migraine completed a psychiatric examination using the structured clinical interview for DSM-IV-R Axis I. The actual prevalence of migraine among these medical students was 12.6 %. The students with a migraine were diagnosed with alexithymia and post-traumatic stress disorder more frequently than those without migraine. The Migraine Disability Assessment Scale scores correlated with the post-traumatic stress disorder scores. The results of this study indicate that migraine was highly prevalent among medical students in Turkey and was associated with the alexithymic personality trait and comorbid psychiatric disorders including post-traumatic stress disorder. Treatment strategies must be developed to manage these comorbidities.